Effect of Ground Motion Orientation on Seismic Responses of an Asymmetric Stress Ribbon Pedestrian Bridge - Yi Zhang; Wuchuan Pu; Qishuo Zhang; Kaiwen Liu; Hua Dong (Advances in Civil Engineering)
The stress ribbon bridge uses ribbon in high tension to transfer loads and exhibits geometric nonlinearity under dynamic earthquake excitations. A typical double-span asymmetric stress ribbon pedestrian bridge was introduced as a prototype, and nonlinear time history analysis was performed to investigate the effect of ground motion orientation on the structural responses. Non-pulse-type and pulse-type ground motions were considered, and the influence of vertical ground motions was investigated. Numerical results showed that the stress ribbon bridge’s vertical and transverse displacements were sensitive to the excitation of the vertical ground motion. No single orientation led to the most critical values in all response indexes, and the critical orientation was approximately independent of the vertical ground motion. The negative bending moment of the ribbons, the pier top displacement, and the pier base moment at the transverse direction were sensitive to the ground motion orientation. Checking the responses resulting from different directions is necessary for a comprehensive estimation of the seismic performance of the stress ribbon bridge.